Deterioration of irradiation/high-temperature pretreated, linear low-density polyethylene (LLDPE) by Bacillus amyloliquefaciens. (August 2018) - Novotný, Čeněk; Malachová, Kateřina; Adamus, Grażyna; Kwiecień, Michał; Lotti, Nadia; Soccio, Michelina; Verney, Vincent; Fava, Fabio
Abstract: A Bacillus amyloliquefaciens strain was isolated from composted plastics and identified using microbial identification system BIOLOG and 16S rDNA sequences. The capability to attack virgin and ɣ-irradiation/high temperature-pretreated LLDPE films was investigated for comparison to evaluate the effect of pretreatment. A biodeteriorating effect characterized by low weight reductions of 1.1 ± 0.3 to 3.2 ± 1.3% was observed with the pretreated LLDPE within 40–60 days. The precision of the gravimetric method was sometimes negatively affected by the fragmentation of plastic films during the biological treatment or by traces of microbial biofilm firmly adhering to the plastic material. FTIR spectra before and after 60-day treatment indicated a decrease of carbonyl band and flattening of the 1300-1100 cm −1 zone due to bacterial action. GPC showed an increase of Mn and Mw of 2300–3700 and 32 200–35 500 g mol −1, respectively, and a decrease of polydispersity index suggesting presence of low molar weight LLDPE oligomers in pretreated LLDPE. The analysis of crystallinity and melting enthalpy detected the removal of oligomers during biodeterioration. ESI-MS analysis of the medium after 60-day biotreatment of pretreated LLDPE showed a presence of 3-hydroxybutyrate oligomers linked to the disappearance of low molar weight LLDPE oligomers that was not observed with virgin LLDPE. Coincidence of the removal of LLDPE oligomers and the appearance of 3-hydroxybutyrate oligomers suggested metabolization of low molecular LLDPE fractions present in the pretreated LLDPE by B. amyloliquefaciens . The experiments with virgin LLDPE demonstrated a positive effect of the pretreatment. Graphical abstract: Highlights: A Bacillus amyloliquefaciens strain was isolated from composted plastics material. Bacterium was used for treatment of ɣ-irradiation/high temperature-pretreated LLDPE. Physico-chemical analyses brought evidence of a biodeterioration action. Low molar weight LLDPE oligomers disappeared after exposure to B. amyloliquefaciens . Findings suggested metabolization of low molecular LLDPE fraction by the bacterium.